Newborn screening for SCID and severe T- and B-cell lymphopenia in Ukraine: the first analysis of the results, 2022–2025 - Boyarchuk, Oksana; Makukh, Halyna; Volokha, Alla; Bondarenko, Anastasiia; Mytsyk, Nataliia; Barvinska, Oksana; Shymanska, Ivanna; Pohuliai, Yuliia; Veropotvelyan, Mykola; Haviley, Anastasia; Hurina, Marharyta; Romanyshyn, Yaryna; et al. (Frontiers in Immunology, 2025)
IntroductionSevere combined immunodeficiency (SCID) and other profound T- and B-cell lymphopenias are life-threatening conditions that benefit from early diagnosis and treatment. In October 2022, Ukraine launched a nationwide newborn screening (NBS) program for SCID using the T-cell receptor excision circle/kappa-deleting recombination excision circle/spinal muscular atrophy (TREC/KREC/SMA) assay, despite ongoing war-related challenges. The aim of this study was to analyze the results of the SCID NBS program in Ukraine, evaluate its effectiveness, and outline the current challenges and future directions for its development.MethodsWe analyzed data of screened newborns for SCID and related lymphopenias using the TREC/KREC/SMA assay from October 2022 to April 2025. The results of lymphocyte flow cytometry values, genetic testing, and clinical management of patients with positive TREC/KREC results were evaluated.ResultsAmong 398,415 screened newborns, 57 were identified with positive results (32 TREC ± KREC and 25 only KREC). The program demonstrated a high diagnostic yield, with an overall referral rate of 0.01%. In total, 18 newborns with inborn errors of immunity were diagnosed due to NBS (7 SCID/leaky SCID and 11 non-SCID). One case of ZAP70 deficiency was missed due to normal levels of T cells. The incidence of SCID/leaky SCID detected by NBS was 1 in 57,000 live births, and 1 in 49,800 live births when all diagnosed cases, including one initially missed case, were taken into account, which is comparable to data from other countries. All patients with SCID/leaky SCID identified by NBS received hematopoietic stem cell transplantation, with a survival rate of 85.7%. Nijmegen breakage syndrome was the most common syndromic cause of non-SCID T-cell lymphopenias (three cases). The use of the KREC assay enabled the first-time identification in Ukraine of B-cell lymphopenias associated with variants in IGLL1 gene.ConclusionsThe nationwide NBS program in Ukraine demonstrated high sensitivity and specificity in detecting SCID, with a low referral rate and high survival rates among diagnosed patients.